G372(P) Improving cdu for patients, families and medical professionals; a multi-stream quantitative and qualitative project. (24th May 2017) - Popli, G; Brettle, E; Taylor, R; Barnett, N; Edwards, N; Zahir, F; Tharrayil, B; Bassett, E; Jyothish, D
Abstract : Aim: Identify and improve limitations to patient flow, patient and staff experience in the Clinical Decision Unit (CDU-analogous to PAU) in a tertiary children's hospital. Methods and Outcomes: Quantitative data Trends of attendance: hours, days, week and months. The monthly attendance of patients ranged from 382 in July to 716 in December, indicating 200% variation. The daily attendance peaks twice around 12 and 6 pm, a trend maintained throughout the year. Key times: Average time to triage ranged 4 to 25 min, and junior review 74 to 168 min, increasing thoughout the day. Average time to senior review ranged from 50 to 72 min, least when 2 senior personnel present (between 2–6pm) 20% (32/156) patients were non-urgent reviews, 20% were ED/tertiary care reviews from other ED's.Qualitative data (key findings); Surveys with approval of the patient experience team.Patient survey (n=22) 80% pleased with nursing care, medical care, overall experience 55% agreed that their child was seen in timely fashionNursing Survey (n=29) 27%–60% surveyed agreed they could undertake observations, interventions, discharge or transfer in a timely manner. 30%–58% agreed they enjoyed working in CDU or felt well supportedPractitioner survey 50%–66% agreed patients received observations, intervention, discharge or transfer in a timely manner. 81% agreed lack of nursing support affects patient experienceBig 6Identified and developed management guidelines for commonest conditions, and gained approval by CCG for implementation in primary care. Changes implemented: Rearrangement of consultant shifts Additional CDU registrar Deployment of additional nurse from the ED pool as a floater to allow seamless and timely intervention and transfer or discharge. Consideration of a phone advice service. Development of Big 6 Conclusion: Our data helped to lever changes towards improving flow, patient and staff experience. We undertook this significant exercise in one summer, implementing changes to improve the patient and staff journey in readiness for the winter. We aim to repeat our key times and surveys to measure the improvement.